Patient perspectives on factors influencing active surveillance adherence for low‐risk prostate cancer: A qualitative study - Lalita Subramanian; Sarah T. Hawley; Ted A. Skolarus; Aaron Rankin; Michael D. Fetters; Karla Witzke; Jason Chen; Archana Radhakrishnan (Cancer Medicine, 2024)
Abstract Background Prostate cancer is the most common cancer among men in the United States. Treatment guidelines recommend active surveillance for low‐risk prostate cancer, which involves monitoring for progression, to avoid or delay definitive treatments and their side effects. Despite increased uptake, adherence to surveillance remains a challenge. Methods We conducted semi‐structured, qualitative, virtual interviews based on the Theoretical Domains Framework (TDF), with men (15) who were or had been on active surveillance for their low‐risk prostate cancer in 2020. Interviews were transcribed and coded under TDF's behavioral theory‐based domains. We analyzed domains related to adherence to surveillance using constructivist grounded theory to identify themes influencing decision processes in adherence. Results The TDF domains of emotion, beliefs about consequences, environmental context and resources, and social influences were most relevant to surveillance adherence‐. From these four TDF domains, three themes emerged as underlying decision processes: trust in surveillance as treatment, quality of life, and experiences of self and others. Positive perceptions of these three themes supported adherence while negative perceptions contributed to non‐adherence (i.e., not receiving follow‐up or stopping surveillance). The relationship between the TDF domains and themes provided a theoretical process describing factors impacting active surveillance adherence for men with low‐risk prostate cancer. Conclusions Men identified key factors impacting active surveillance adherence that provide opportunities for clinical implementation and practice improvement. Future efforts should focus on multi‐level interventions that foster trust in surveillance as treatment, emphasize quality of life benefits and enhance patients' interpersonal experiences while on surveillance to optimize adherence.